Small Bowel Intussusception due to Metastasized Sarcomatoid Carcinoma of the Lung: A Rare Cause of Intestinal Obstruction in Adults. (30th December 2012) - Guner, Ali; Karyagar, Savaş; Livaoglu, Ayten; Kece, Can; Kucuktulu, Uzer
Abstract : Although small bowel intussusception is one of the most common abdominal emergencies in childhood, it is rare in adults and usually occurs as a result of an underlying pathology. Sarcomatoid carcinoma, a very rare subtype of lung cancer, rarely metastasizes to small bowel and causes complications. In this paper, we aim to describe a patient with small bowel intussusception caused by an isolated small bowel metastasis of the sarcomatoid carcinoma of the lung by reviewing the literature.